A HIGH SCALE SARS-COV-2 PROFILING BY WHOLE-GENOME SEQUENCING USING OXFORD NANOPORE TECHNOLOGY IN KAZAKHSTAN - Amanzhanova, Amina (Nazarbayev University School of Sciences and Humanities, 2022)
Severe acute respiratory syndrome (SARS-CoV-2) is responsible for the worldwide pandemic COVID-19. The original viral whole-genome was sequenced by a high throughput sequencing approach from the samples obtained from Wuhan, China. Real time gene sequencing is the main parameter to manage viral outbreaks because it expands our understanding of virus proliferation, spread, and evolution. Primarily, it relies on the prompt sequencing technique of viral genome immediately from the clinical specimens without the necessity of viral culturing step. Whole-genome sequencing is critical for SARS-CoV-2 variant surveillance, the development of new vaccines and boosters, and the representation of epidemiological situations in the country. A significant increase in the number of COVID-19 cases confirmed in August 2021 in Kazakhstan facilitated a need to establish an effective and proficient system for further study of SARS-CoV-2 genetic variants. The SARS-CoV-2 whole-genome was sequenced using the SARS-CoV-2 ARTIC protocol (EXP-MRT001) by Oxford Nanopore Technologies at the National Laboratory of Astana, Kazakhstan. The 96 samples kindly provided by the Republican Diagnostic Center (RDC) were collected from individuals in Nur-Sultan city diagnosed with COVID-19 in August 2021 using real-time reverse transcription-quantitative polymerase chain reaction (RT-qPCR). All samples had a cycle threshold (Ct) value below 20 with an average Ct value of 13.88. The genomic coverage of the sequenced samples was ~99.8% and 77 out of 96 (80%) samples that passed quality control are deposited in the Global initiative on sharing all influenza data (GISAID). The AY.122 (n=69), B.1.617.2 (n=6), and AY.89 (n=1) delta lineages, and one sample B.1.637 belongs to a separate lineage corresponding to Iota were detected. To the best of our knowledge, this is the first study of SARS-CoV-2 whole genome sequencing by the ONT approach in Kazakhstan. The performed work confirms that ONT sequencing is a robust technique for the monitoring of SARS CoV-2 new variants by its whole genome sequencing. Also, established genomic sequences reveal the novel mutations that alter viral characteristics, particularly, the detected mutations are predicted to increase the spike protein stability by computational tools. The further high-throughput analysis and SARS-CoV-2 surveillance in the country are expected by the GridION at National Laboratory of Astana (NLA) at Nazarbayev University at a larger scale
Keywords: Type of access: Open Access; SARS-CoV-2; Oxford Nanopore Technology